Bedaquiline Targets the ε Subunit of Mycobacterial F-ATP Synthase - Kundu, Subhashri (2017)
The tuberculosis drug bedaquiline inhibits mycobacterial F-ATP synthase by binding to its c subunit. Using the purified ε subunit of the synthase and spectroscopy, we previously demonstrated that the drug interacts with this protein near its unique tryptophan residue. Here, we show that replacement of ε's tryptophan with alanine resulted in bedaquiline hypersusceptibility of the bacteria. Overexpression of the wild-type ε subunit caused resistance. These results suggest that the drug also targets the ε subunit.